Nurses' Roles and Challenges to Providing Care for Tropical Diseases: A Scoping Review - Fithriyyah, Yayu Nidaul; Haryani, H (Jurnal Berita Ilmu Keperawatan, 2022)
Tropical diseases are associated with tropical regions, but global access travel, climate change, and environmental factors affecting disease vectors may spread to non-endemic countries. This review reinforces the view of nurses' roles and challenges to providing care for tropical diseases. This scoping review search included: SCOPUS, PubMed, EBSCO Medline, Science Direct, and citation search: Google Scholar. Studies included if the population was nurses or part of a multidisciplinary or provider intervention on tropical diseases and original English articles between 2011 and 2021 with various methods. From 773 studies identified, 23 met the inclusion criteria. Three themes emerged: 1) nurses role as health providers, educators, motivators, leaders, collaboration, and coordination; 2) providing safe working and job satisfaction; and 3) The role of organizations, health systems, and policymakers. There were also three challenges: 1) lack of skills, knowledge, and training for nurses, 2) the stigma of tropical diseases, 3) sociocultural approach. The role and practice of nursing in tropical diseases vary across healthcare settings, influenced by nurses' stigma, knowledge, training, job safety, and satisfaction. Nurse lack knowledge and training compared to other health workers. Potential to increase nurse participation with a sociocultural approach and involving nurse's leadership roles require further research